Work and Power Analysis of the Golf Swing - Nesbit, Steven M. (Asist Group, 2005)
A work and power (energy) analysis of the golf swing is presented as a method for evaluating the mechanics of the golf swing. Two computer models were used to estimate the energy production, transfers, and conversions within the body and the golf club by employing standard methods of mechanics to calculate work of forces and torques, kinetic energies, strain energies, and power during the golf swing. A detailed model of the golf club determined the energy transfers and conversions within the club during the downswing. A full-body computer model of the golfer determined the internal work produced at the body joints during the downswing. Four diverse amateur subjects were analyzed and compared using these two models. The energy approach yielded new information on swing mechanics, determined the force and torque components that accelerated the club, illustrated which segments of the body produced work, determined the timing of internal work generation, measured swing efficiencies, calculated shaft energy storage and release, and proved that forces and range of motion were equally important in developing club head velocity. A more comprehensive description of the downswing emerged from information derived from an energy based analysis.